2019
DOI: 10.14202/vetworld.2019.1390-1394
|View full text |Cite
|
Sign up to set email alerts
|

Ectoparasites of brown rats (Rattus norvegicus) in Grenada, West Indies

Abstract: Background and Aim:Arthropod ectoparasites (mites, lice, ticks, and fleas) on common house rats or brown rats (Rattus norvegicus) are known to transmit zoonotic pathogens and diminish rat health. To the best of our knowledge, there is no published information regarding the prevalence of ectoparasites on R. norvegicus in Grenada. This study aimed to determine the prevalence and types of ectoparasites present on brown rats from Grenada.Materials and Methods:One hundred sixty-eight rats were collected live from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
1
3
0
1
Order By: Relevance
“…were similar to those reported byThille et al (2019) who found that adults of R. norvegicus were the most infested by ectoparasites, with a prevalence of 90.7%, compared to juveniles (66.7%) with a significant difference (P = 0.008). Volf (1991) maintained that there is a relation between the level of infection of rats with the louse Polyplax spinulosa and the age and gender of rats.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…were similar to those reported byThille et al (2019) who found that adults of R. norvegicus were the most infested by ectoparasites, with a prevalence of 90.7%, compared to juveniles (66.7%) with a significant difference (P = 0.008). Volf (1991) maintained that there is a relation between the level of infection of rats with the louse Polyplax spinulosa and the age and gender of rats.…”
supporting
confidence: 90%
“…which are dangerous to human health, due to the fact that they participate in the distribution of various pathogens zoonoses like Rickettsia spp. and transferring pathogenic agents to hosts causing diseases to human beings (Crystal, 1958;Lehan, 2005;Badiaga and Brouqui, 2012;Chakma et al, 2015;Thille et al, 2019). Also, X. cheopis was considered the main epidemic and enzootic vector of murine typhus Rickettsia typhi (Soliman et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…felis, Myobia spp., Mesostigmata, Argasidae, Atopomelidae dan Listrophoridae. 6 Endoparasit yang diketahui menginfeksi tikus, antara lain Protozoa (Giardia muris, Entamoeba muris, Blastocystis spp., Eimeria spp., Trichomonas muris, Cryptosporidium spp., 7 Klossiella muris, K. cobayae 8 ), dan Helminth (Hymenolepis nana, Syphacia obvelata, Strongyloides ratti, Trichomonas crassicauda, Aspiculuris tetraptera, 7 Hymenolepis diminuta, 9 S. muris, 7,10 Nippostrongylus muris, 8 Eustrongylides excisus, 11 Gongylonema neoplasticum, 8 dan Cysticercus fasciolaris. [12][13][14] Keberadaan tikus laboratorium sangat diperlukan guna kepentingan penelitian biomedis atau observasi laboratorium.…”
Section: Ctenocephalidesunclassified
“…In a very recent study, we reported several opportunistic and pathogenic bacteria, including Bordetella, Clostridium, Corynebacterium, Empedobacter, Helicobacter, Limosilactobacillus, Macrococcus, Neisseria zaloph, Porphyromonas, Pseudomonas, Rahnella, Ralstonia, Rhodococcus, Rickettsiella, Streptococcus, etc. in the free-living urban R. norvegicus (Shah et al, 2023). R. norvegicus is also reported to be a host for a large number of blood-sucking ectoparasites, such as Polyplax lice, fleas, fur mites, mesostigmatid mites, etc., in the West Indies (Thille et al, 2019). Another study investigated free-living R. norvegicus for the presence of zoonotic viruses, parasites, and bacteria in Maryland, United States (Easterbrook et al, 2007).…”
Section: Introductionmentioning
confidence: 99%